Remyelination in experimentally demyelinated connexin 32 KnockOut mice Remielinização em camundongos KnockOut para conexina 32 desmielinizados experimentalmente - Adriano Tony Ramos; Paulo César Maiorka; Maria Lúcia Zaidan Dagli; Fernando Yutaka Moniwa Hosomi; Kalan Bastos Violin; Andréa Latorre; Aline de Marco Viott; Eduardo Kenji Masuda; Maria Elisa Trost; Tessie Beck Martins; Dominguita Lühers Graça (Arquivos de Neuro-Psiquiatria)
The aim of this study was to evaluate the role of connexin 32 (Cx 32) during remyelination of the peripheral nervous system, through a local injection of either 0,1% ethidium bromide solution or saline in the sciatic nerve of Cx 32 knockout mice. Euthanasia was performed ranging from 1, 2, 3, 7, 15, 21 to 30 days after injection. Histochemical, immunohistochemical, immunofluorescence and transmission electron microscopical techniques were used to analyze the development of the lesions. Within the sciatic nerves, Schwann cells initially showed signs of intoxication and rejected their sheaths; after seven days, some thin newly formed myelin sheaths with uneven compactness and redundant loops (tomacula) were conspicuous. We concluded that the regeneration of lost myelin sheaths within the PNS followed the pattern already reported for this model in other laboratory species. Therefore, these results suggest that absence of Cx 32 did not interfere with the normal pattern of remyelination in this model in young mice. Este estudo visou avaliar o papel da conexina 32 (Cx 32) durante a remielinização no sistema nervoso periférico. Uma injeção local de 0,1% de solução de brometo de etídio foi realizada no nervo ciático de camundongos deletados para a Cx 32, com eutanásia dos animais aos 1, 2, 3, 7, 15, 21 e 30 dias pós-injeção. Avaliações histoquímicas, imunoistoquímicas, por imunofluorescência e por microscopia eletrônica de transmissão foram utilizadas na análise do desenvolvimento das lesões. Nos nervos ciáticos, células de Schwann mostraram inicialmente sinais de intoxicação e rejeitaram suas bainhas. Após sete dias, observaram-se finas bainhas neoformadas, com compactação desigual e alças redundantes (tomácula). Conclui-se que a regeneração de bainhas de mielina perdidas no SNP seguiu o padrão já relatado deste modelo em outras espécies de laboratório. Portanto, estes resultados sugerem que a ausência da Cx 32 não interferiu com o padrão normal de remielinização em camundongos jovens neste modelo.